Management of persistent postconcussion symptoms in youth: a randomised control trial protocol. Issue 7 (31st July 2015) - Reed, Nick; Greenspoon, Dayna; Iverson, Grant L; DeMatteo, Carol; Fait, Philippe; Gauvin-Lepage, Jérôme; Hunt, Anne; Gagnon, Isabelle J
Abstract : Introduction: Current management of concussion consists of early education, rest until symptom free, with gradual return to school and physical activity protocols. Although this management strategy is effective for most youth who sustain a concussion, it is not an appropriate strategy for youth with persistent postconcussion symptoms. Prolonged rest and periods of restricted activity may place youth at risk for secondary issues and contribute to the chronicity of postconcussion symptoms. The purpose of this study is to evaluate the efficacy of an active rehabilitation protocol for youth who are slow to recover from concussion. It is hypothesised that an active rehabilitation intervention can reduce persistent postconcussion symptoms, improve function and facilitate return to activity. This article describes the research protocol. Methods and analysis: This is a randomised clinical trial with blinded outcome measurement. Participants will be recruited and randomly assigned to 1 of 2 treatment groups, an active rehabilitation intervention or a standard care education group. Both groups will receive standard care education. However, the active rehabilitation group will participate in an additional low-intensity exercise programme consisting of aerobic, coordination and visualisation exercises. Both the active rehabilitation and the standard care education interventions will be 6 weeks in duration. The primary outcome measure is postconcussion symptoms. Secondary outcome measures include functional recovery (cognitive, motor, psychosocial and emotional functioning) and return to activity. Outcome measures will be administered preintervention and postintervention. The primary outcome measure will also be repeated 2 weeks into the intervention period. Ethics and dissemination: This study has been approved by the Holland Bloorview Kids Rehabilitation Hospital research ethics board (REB # 13-459). The findings from this study will be shared with the general public, sport associations, relevant brain injury organisations and healthcare professionals. Trial registration number: NCT02257749.